Progress for Integrated Coastal Zone Management in the Caribbean of Guatemala - Caviedes, Verónica (2021)
[Introduction]: The response to the processes of appropriation and unsustainable use of the Guatemalan coast was addressed in 2009 by the Policy for the Integrated Management of Coastal Marine Areas. [Objectives]: This research aims to establish the current implementation status of Integrated Coastal Zone Management (ICZM) with emphasis on the Caribbean of Guatemala. [Methodology]: First, this article shows the characterization of the problems in the coastal zone by applying the DAPSIR method. The diagnosis of its legal-administrative subsystem related to the ICZM is presented below. In this case, the Methodology followed is the Decalogue for Integrated Coastal Management, analyzing ten key aspects of the public policies in that space. [Results]: Despite the progress made, the 2009 Marine Policy has not yet been implemented, and there are no plans and strategies for the ICZM on the Caribbean coast. Furthermore, the development of key strategic initiatives for marine research and non-governmental organizations is evident. [Conclusions]: The efforts made in recent years point to a positive trend; however, the Marine Policy must be retaken and have an operational plan.